2017
DOI: 10.1539/joh.17-0002-oa
|View full text |Cite
|
Sign up to set email alerts
|

Exposure assessment of carbon nanotubes at pilot factory focusing on quantitative determination of catalytic metals

Abstract: Objectives: The application of multiwall carbon nanotubes (MWCNTs) currently extends to various fields. However, it has been reported that exposure to CNT causes hazardous effects on animals and cells. The purpose of this study was to quantify the exposure to MWCNT in MWCNT/polymer composites for exposure assessment. We focused on catalytic metals included in the MWCNT and the diameter of dust released during the working processes. Although the Co in MWCNTs is not a common catalyst, it was used as a tracer in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…An alternative monitoring method of airborne CNTs could have been elemental analysis of catalytic metals in the CNTs collected during filter sampling ( Maynard et al , 2004 ; Kato et al , 2017) . Analysis in the previously mentioned studies showed that the CNTs contained traces of different metal, such as Fe, Mo, Al, and Co.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An alternative monitoring method of airborne CNTs could have been elemental analysis of catalytic metals in the CNTs collected during filter sampling ( Maynard et al , 2004 ; Kato et al , 2017) . Analysis in the previously mentioned studies showed that the CNTs contained traces of different metal, such as Fe, Mo, Al, and Co.…”
Section: Discussionmentioning
confidence: 99%
“…The existing literature includes a few earlier studies of emission and exposure in connection to CNT composite production ( Cena and Peters, 2011 ; Fleury et al , 2013 ; Thompson et al , 2015 ; Kato et al , 2017) , as well as studies of machining processes such as sanding and sawing of CNT composites ( Bello et al, 2009 , 2010 ; Cena and Peters, 2011 ; Wohlleben et al , 2013 ; Ding et al , 2017 ; Kuijpers et al , 2019 ; Ogura et al , 2019 ). There is high-quality evidence that workers are occupationally exposed to CNTs during production of CNTs, mainly in handling tasks such as pouring, weighing, mixing, harvesting, extruding, sonication, and packaging of CNT powder or liquid suspensions ( Debia et al , 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…While Y was chosen as the surrogate trace residual metal in this study, each MWCNT will have distinctive synthesis methods [26,38,39] and thus will likely have unique trace residual metal compositions. Consequently, other researchers used Y or different trace elements to track CNTs (e.g., Co, Ni, Mo) [15,16,17,18,19,20,21,22]. It will be important to understand these differences between MWCNTs and whether a unified method can be developed to quantify MWCNTs through spICP-MS or ICP-MS using trace residual metals or whether trace residual metals like Y can be useful as a marker in standardized testing of MWCNTs moving forward.…”
Section: Discussionmentioning
confidence: 99%
“…Current analytical techniques to detect and quantify carbon nanoparticles include programmed thermal analysis (PTA), Raman spectroscopy, UV-visible spectrophotometry, and microwave treatment with thermal analysis, but most available techniques have detection limits in solid matrices and water on the order of 10–100 mg kg −1 or 0.1–10 mg L −1 , respectively [14]. Recent studies evaluated the ability of single particle inductively coupled plasma-mass spectrometry (spICP-MS) to detect residual trace catalytic metals (e.g., Fe, Y, Ni, Co, Mo) that persisted in single- or multi-walled carbon nanotubes (SWCNTs) at ng L −1 levels in an aqueous matrix [15,16,17,18,19,20,21,22,23,24]. Therefore, we explored spICP-MS and ICP-MS directly for the detection of known specific commercial MWCNTs in complex wastewater matrices.…”
Section: Introductionmentioning
confidence: 99%